Teaching English speaking skills to the Arab students in the Saudi school in Kuala Lumpur: problems and solutions - Al-Sobhi, Bandar Mohammad Saeed; Preece, Abdul Shakour Duncan (ustralian International Academic Centre PTY. LTD., 2018)
Of the four English language skills, speaking enjoys a superior status. Accordingly, it should be given high priority while teaching. In spite of its importance, teaching English speaking skill to Arab EFL learners has always been an exacting task for Arab teachers of English because it is considered a foreign language, i.e. not widely spoken or used in everyday interactions. For such a reason, Arab teachers of English are required to persistently implement new teaching strategies to tackle the problems regarding speaking skills in the classroom. Although a number of studies have been carried out to investigate the difficulties related to teaching English language skills to the Arab students in the Arab World, the current study is regarded the first study which highlights the problems in learning and teaching English speaking skill in the Saudi School in Kuala Lumpur where English is actively spoken as a second language. The main objective of this paper is to investigate the common problems which affect the teaching of English speaking skills to the Arab learners in the Saudi School in Kuala Lumpur. Additionally, it aims at exploring the areas of difficulty that prevent the Arab students from learning to speak in the English classes. This research also scrutinises the role of Kuala Lumpur ESL context on the Arab students’ English language speaking skills. The current study adheres to qualitative method, and its data were collected via classroom observations and face-to-face interviews with four teachers of English and four students selected purposively. Findings included areas like learning and teaching difficulties. The study suggested some techniques to improve the teaching quality and enable the students to overcome their lack of speaking ability such as implementing communicative approach in the English classes.